Meningkatkan Semangat Berwirausaha Melalui Pemanfaatan Digital Marketing Pada Produksi Kopi Ratu Luwak Liwa Lampung Barat - Wellfarina Hamer; Nur Azmi Rohimajaya; Wellian Hamer; Nasiruddin (Jurnal Pengabdian Pada Masyarakat, 2022)
IMPROVING ENTREPRENEURSHIP SPIRIT THROUGH THE UTILIZATION OF DIGITAL MARKETING IN RATU LUWAK COFFEE PRODUCTION, LIWA WEST LAMPUNG. The study of entrepreneurial development is currently being discussed in various forums around the world because it is related to efforts to build the economy on a regional and national scale. The world is faced with a very big problem, namely the emergence of the COVID-19 pandemic which of course has an impact on many things, this issue is also relevant to the current objective conditions in Indonesia as one of the countries affected, especially on the economic aspect. Indonesia, which is dominated by Micro, Small, and Medium Enterprises (UMKM) needs to pay special attention to this sector because the contribution of UMKM to the national economy is quite large. This community service activity aims to explore the entrepreneurial spirit and also increase sales through the use of digital marketing, namely by providing an understanding of the importance of entrepreneurship, marketing strategies, and attractive product packaging to direct practice of making online stores as well as using the web and social media to increase sales. By utilizing this digital marketing strategy, local UMKM is expected to be able to reach a wider market and of course, the managed business can also be recognized so that it can inspire many people in entrepreneurship.